A feminist analysis of organizational research on sex differences - Ely, Robin; Padavic, Irene (Academy of Management Review, 2007)
Based on a survey of empirical research on gender in organizations published over a twenty-year period, we argue that, cumulatively, studies of sex difference tend to neglect organizational features. Drawing on concepts from feminist theory about gender as a system, as identity, and as power, we outline how greater attention to the links between gender identity and organizational structures and practices would enrich the field. We conclude with a research agenda that retains a focus on the individual while incorporating an analysis of the impact of organizations.